Multi Lane Free Flow Policy Analysis Based On Public Service And Public Administration Legal Studies - Hidayat, Fanni Athar; Kurniawan, Teguh (Universitas Muhammadiyah Sumatera Utara, 2024)
Policy Multi Lane Free Flow is desired policy launched by the government for increase internal public services government. Policy that's what comes next give something description that in implementation public service is responsibility from government and is room scope from implementation law state Administration No only That of course, government in create policy and planning about multi lande free flow endeavor is including in territory and space scope from service subject and object law state administration. Subject and object state administration due to later policy the will issued in form a Decision and/ or Decree / Beschiking which is part from state Administration. That's what happens next No can denied. Function from law internal state administration service public as form base legitimacy a Subject of Service Law public in do duties and responsibilities. State administrative law will review from formation policy and enforcement decision as well as its implementation